UJI FISIK SABUN CAIR EKSTRAK ANGGUR LAUT (Caulerpa sp) DAN EFEKTIVITAS TERHADAP PERTUMBUHAN Candida albicans - Sugiarti, Lilis; Palupi, Dian Arsanti; Susiloningrum, Dwi (Cendekia Journal of Pharmacy, 2025)
Vaginal discharge is excessive fluid discharge from the vagina which is caused by Indonesia's humid temperatures making it easy to become infected with the fungus Candida albicans. One alternative way to overcome this is with natural ingredients, namely sea grapes which contain chemical compounds in the form of alkaloids, flavonoids, saponins and tannins. The aim of this research was to determine the antifungal activity of sea grape liquid soap (Caulerpa sp) against Candida albicans. Sea grapes (Caulerpa sp) were extracted using the UAE method with 70% ethanol solvent. The extract was formulated into liquid soap with formula 0 (0%), formula 1 (8%) and formula 2 (16%) which were tested against the Candida albicans fungus using the well diffusion method with control (+), namely Resik V Godokan Sirih. The research results obtained on sea grape liquid soap (Caulerpa sp) can inhibit Candida albicans with the diameter of the inhibition zone of formula 0, formula 1 and formula 2 respectively 5.9 ± 0.177 mm (weak); 9.62 ± 0.180 mm (weak) and 10.14 ± 0.404 mm (moderate). Control (+) had an inhibition zone diameter of 19.66 ± 0.499 (strong). The optimum formula for sea grape extract liquid soap (Caulerpa sp) in inhibiting Candida albicans is formula 1.